Influence of surface modifiers on hydrothermal synthesis of KxNa(12x)NbO3 - Ramajo, Leandro Alfredo (2015)
The synthesis of potassium–sodium niobate lead-free piezoelectric ceramics has been widely studied during the past decade because of the promising industrial application of these materials. We here report the effect of different additives or surface modifiers (such as cetyltrimethylammonium bromide, hexamethylenetetramine, and Triton X-100) on the synthesis of KxNa1−xNbO3 by a hydrothermal process. To achieve this purpose, ceramic powders are prepared using a 0.6 KOH/NaOH ratio, with a total OH− concentration of 8N under hydrothermal conditions at 200 °C. Surface modifiers are used aiming to avoid agglomeration, to modify the particle surface morphology and to improve the sample density after sintering. It is worth to note that the potassium concentration in KxNa(1−x)NbO3 was increased by the incorporation of the surface modifiers. In this way, KxNa1−xNbO3-based ceramics exhibit enhanced electrical properties.